Case study of safety management in construction industry - Nur Mashita, Ahmad (2019)
High accident rate in construction is a universal problem which needs to be tackled by all parties concerned (Poon et al. 2008). Although regulation in occupational safety and health in Malaysia are quite comprehensive and reinforced with strict safety inspection and audit by Department of Occupational Safety and Health Malaysia (DOSH) at regular of time, the accident and fatality still at unacceptable figure. The construction industry in confront with a poor level of safety performance and dangerous safety issues that may cause injuries and death due to the major cause of unethical attitude and behaviour factors which leads to other problems occur in occupational safety and health. Objective of this study is to study the safety issues that happen in construction industry, to identify the major cause of safety issue that happen in construction industry and to analyse solution to overcome the issues in safety management. This study was carried out by literature review and questionnaire survey to achieve the objectives. The information related to the safety management in construction industry has been collected from journal, internet and published book. The questionnaire had been distributed to a total of one hundred respondents that are actively involved in construction industry all over Malaysia. Through this study, it can be identified that the Top three common issue in construction is insufficient proper training and education, not everyone aware of the contents of safety policy and site does not kept neat and tidy. In order to minimize the problem, top management must establish safety training and orientation for site operatives and safety officer’s should provide advice on actions to be taken in order to ensure a safer working environment.